Radial consolidation of soil layer under truncated cone fill. Issue 1 (February 2015) - Ganesalingam, Dhanya; Read, Wayne; Sivakugan, Nagaratnam
Abstract : A given quantity of fill may be placed over a given circular area in the shape of a cone, a truncated cone, with nearly uniform thickness. Depending on the shape of the fill, different non-uniform initial excess pore water pressure distributions can exist in the underlying saturated soil layer. This paper investigates the influence of the shape of the fill on the time-dependant consolidation behaviour of the underlying circular soil layer, which is draining only along a peripheral drain. Plots of the average degree of consolidation against time factor and degree of consolidation isochrones are developed for different axisymmetric embankment geometries. The results show that the way the load is spread within the circular area has significant influence on the rate of pore water pressure dissipation throughout the soil layer. The exact degree of consolidation at a point within the clay is computed to illustrate the variation in the degree of consolidation with the radial distance.